GRANITOID MAGMATISM IN THE NORTH OF THE URALS: U–Pb AGE, EVOLUTION, SOURCES - O. V. Udoratina; K. V. Kulikova; A. S. Shuyskiy; A. A. Sobolevа; V. L. Andreichev; I. I. Golubeva; V. A. Kapitanova (Геодинамика и тектонофизика, 2021)
This work presents the summarization of U–Pb (SIMS, TIMS) zircon dates and petrogeochemical signatures of granitoids of the north of the Urals (Polar, Subpolar, and Northern Urals) obtained over the last decade. Granitе melts were formed from melting of different substrates, highly heterogeneous in composition and age, at all geodynamic stages distinguished in the studied area. Preuralides include island arc–accretionary (735–720 Ma, 670 Ma), collisional (650–520 Ma), and rift-related (520–480 Ma) granitoids. Uralides includes primitive island-arc granitoids (460–429 Ma), mature island-arc granitoids (412–368 Ma), early collisional (360–316 Ma) and late collisional (277–249 Ma) granitoids. As a result, the general trend of variations of oxygen (δ18OZrn, ‰), neodymium (εNd(t)wr), and hafnium (εHf(t)Zrn) isotope compositions identified in time. Mantle isotope compositions (δ18OZrn (+5.6), εNd(t)wr (+1.7), εHf(t)Zrn (+8.7...+10.6)), common for island arc granitoids (Preuralides) are changed by crustal–mantle ones (δ18OZrn (+7.2...+8.5), εNd(t)wr (–4.8...+1.8), εHf(t)Zrn (+2.1 to +13)), typical of collisional granites. According to this, the crustal matter played a significant role during the formation of the latter. The crustal-mantle isotope compositions are changed by the mantle ones, characteristic of rift-related (δ18OZrn (+4.7...+7), εNd(t)wr (+0.7...+5.6), εHf(t)Zrn (–2.04...+12.5)) and island-arc (Uralides; δ18OZrn (+4.2...+5.7), εNd(t)wr (+4.1...+7.4), εHf(t)Zrn (+12...+15.2)) granitoids.